Penguatan Karakter dan Moderasi Beragama melalui Program Pembinaan Guru dan Santri Dayah Darussa’adah - Ishaq; Liza Arisna Rahman (BA: Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to describe the efforts of character development and religious moderation through a coaching program for teachers and students at Dayah Darussa’adah, located in Gampong Lhok Panjoe, Darul Ihsan Subdistrict, East Aceh Regency. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation review. The findings indicate that the program effectively instills core character values such as honesty, responsibility, discipline, as well as tolerance, non-violence, and patriotism as components of religious moderation. Teachers play an active role as facilitators and agents of change, while students show a positive response by internalizing these values in their daily lives. This study highlights the significant role of dayah (Islamic boarding schools) in shaping a generation with noble character and a moderate religious perspective, which is essential in the context of national and societal harmony.